The Effect Of Ergonomic Exercises On Reducing Uric Acid Levels In The Elderly - Aris Widiyanto; Wiatma, Deny Sutrisna; Krisnanda Aditya Pradana; Perdana Prabasari Putri Ichsani; Santy Irene Putri; Ayu Anulus; Trisakti Halimah Delimasari; Joko Tri Atmojo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Health problems occur in the elderly due to a decrease in body function, one of which is a decrease in musculoskeletal function, namely Arthritis Gout. Ergonomic gymnastics is a physical activity that can help lower uric acid levels. This study aims to determine the effect of ergonomic gymnastics on uric acid levels in the elderly. The research uses a quantitative design with a pretest-postest group with control group design. The sample consisted of 30 elderly people who were selected by random sampling. The research instrument is the assessment of uric acid levels carried out before and after the intervention is given. The research analysis consisted of univariate analysis and bivariate analysis using the Mann Whitney test with STATA software version 17. The results of the analysis showed that the mean uric acid level was 6.34 ± 0.97, before intervention and the mean decreased to 5.30 ± 0.7, after intervention. There was an effect of ergonomic gymnastics on the reduction of uric acid levels in the elderly with a Mann-Whitney p-value test of 0.0001. Ergonomic gymnastics can be a non-pharmacological treatment option to lower uric acid levels in the elderly. Ergonomic gymnastics can lower uric acid levels with muscle relaxation which can improve the process of reabsorption of uric acid in the urine. The application of ergonomic gymnastics 3 times a week showed a significant difference in uric acid levels in the elderly.